Mengukur kesuksesan website Rumah Sakit Darmo Surabaya menggunakan model Delone dan Mclean - Wulansari, Anita; Prapanca, Juniar Sandra; Inayati, Immah (Universitas Pesantren Tinggi Darul 'Ulum (Unipdu) Jombang, 2021)
Websites is important for services industries, such as hopitals, because it help to deliver the information of services provided by the hospitals to their customers. However, Rumah Sakit Darmo Surabaya has not measure the performance of its website yet. Several studies related to measuring the success of information systems in hospitals use the Delone and Mclean model as a measuring tool. Those researchs have a vary results. Therefore, the purpose of this study is to assess the performance of the Rumah Sakit Darmo Surabaya website and to understand the factors that influence it by adapting Delone and Mclean success model. Respondents of this researh are 130 website visitors. The data obtained through questionnaires were processed using Structural Equation Modeling (SEM) analysis. Out of nine hypotheses proposed, only three can be accepted. This research prove that system quality and service quality affect user satisfaction and that usage affects net benefits.